Pragmatic Presupposition: An ExtraLinguisitic Concept (Journal of the College of Languages (JCL), 2014)
Presupposition, which indicates a prior assumption, is a vital notion in both semantic and pragmatic disciplines. It refers to assumptions implicitly made by interlocutors, which are necessary for the correct interpretation of an utterance. Although there is a general agreement that presupposition is a universal property of Language, there are various propositions concerning its nature. However, this research work proposes that presupposition is a contextual term, thus, is more pragmatic than semantic in its nature.Although Semantics and Pragmatics are two distinct disciplines, they are interrelated and complementary to each other, since meaning proper involves both, and since there is no clear borderline between the two disciplines. However, due to the limitations of the research paper, presupposition is dealt with as a contextual notion, thus pragmatically.